Method for testing energy feedback performance of microporous material
By obtaining the sample from the sole and recording the energy absorption and release curves on the test instrument, and calculating the energy feedback ratio HER, the problem of the inability to detect the energy feedback performance of the sole material in the prior art is solved, and the reliability and simplicity of the test are achieved.
Patent Information
- Application Number
- CN202411387096.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art cannot effectively detect the energy feedback performance of sole materials. Energy feedback is of great significance to pushing the ground during exercise and reducing human energy consumption, but there is a lack of effective detection methods.
By obtaining the sample from the sole of the test shoe, peeling and fixing it on the test instrument, falling from the set height using the impact device, recording the energy absorption and release curves, calculating the energy feedback ratio HER, and quantifying the energy feedback performance of the material.
A reliable method for energy feedback performance testing of microporous materials is provided, which simplifies the testing steps and ensures the reliability of measurement results by peeling and limiting the sample thickness, allowing existing shock absorption testing instruments to be used.
Smart Images

Figure CN119223863A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sole material performance testing, and in particular to a method for testing the energy feedback performance of microporous materials. Background Art
[0002] As people's living standards continue to improve, they pay more and more attention to fitness, and at the same time, their requirements for shoes are getting higher and higher. They not only require good appearance and comfort, but also need to have some special functions, such as deodorization, arch protection, shock absorption, etc. For sports shoes, shock absorption is one of its most important performance indicators, and it is necessary to test the shock absorption performance of the sole material.
[0003] In order to ensure the shock absorption performance of the sole, the sole is usually made of microporous materials. At present, the shock absorption performance of the sole material is generally obtained by testing with a shock absorption tester, but the results of the shock absorption tester only characterize the shock absorption performance of the material, that is, the energy absorbed by the sole. The current performance testing of sole materials does not involve the energy feedback performance of the material. Energy feedback refers to the energy that the sole material absorbs and feeds back to the human body. The energy feedback of the sole material can assist in pushing off the ground during exercise, reduce the energy consumption of the human body, and thus improve the athletic performance of athletes, or reduce the fatigue of the wearer. Therefore, in order to characterize the energy feedback performance of the sole material, a set of effective testing methods is urgently needed. Summary of the invention
[0004] The object of the present invention is to provide a method for testing the energy feedback performance of microporous materials, the measurement result of which is reliable and the testing steps are simple.
[0005] To achieve the above object, the present invention discloses a method for testing the energy feedback performance of microporous materials, which comprises the following steps: S1. Obtain the sample from the sole of the test shoe; S2. Peel the sample, and the thickness of the sample after peeling is 25±1mm; S3. Fix the sample on the test instrument and locate the test part of the sample; start the test instrument so that the impact device freely falls from the set height to impact the sample, and repeats N times, where N is a positive integer; the test instrument records the energy absorption curve and energy release curve of the sample during each impact process; S4. Calculate the energy value UM applied by the impact device according to the energy absorption curve of the sample, calculate the energy value UF transmitted back by the sample according to the energy release curve of the sample, and calculate the energy feedback ratio HER of the sample, HER=UF / UM*100%.
[0006] The present invention calculates the energy feedback ratio HER of the sample by obtaining the energy value UF returned by the shock absorption system and the energy value UM applied by the impact test system, and quantifies the calculation method of the material energy feedback ratio (HER). By peeling the sample, the presence of the material surface coating that affects the test results is avoided, and by limiting the thickness of the sample, the measurement results are reliable. In addition, the test steps of the present invention are simple, and the previous shock absorption test instruments can be used.
[0007] Preferably, in step S1, the sample is circular with a diameter of not less than 65 mm, or the sample is square with a side length of not less than 65 mm. Such a setting can ensure that the force on the sample is uniform.
[0008] Preferably, in step S1, the sample is an integral structure or a laminated structure. The sample is preferably an integral structure to facilitate the stability of the test, but the thickness of some soles is less than the required 25±1 mm, so a laminated structure can be used to achieve the required thickness.
[0009] Preferably, in step S3, the mass of the impact device is 8.5-12 kg, the drop height from the impact device to the sample is 50-80 mm, and the impact cycle period is 2±0.1 s.
[0010] Preferably, the impact device comprises a device body, a force sensor and an impact head from top to bottom, the impact head is a cylinder with a diameter of 45±0.1mm, the bottom edge of the impact head is provided with a chamfer with a width of 1.0±0.25mm or a fillet with a radius of 1.0±0.25mm, and the mass of the impact head does not exceed 0.2kg.
[0011] Preferably, step S3 is performed at a temperature of 23±2° C. and a relative humidity of 50±4%.
[0012] Preferably, in step S3, the impact cycle is performed 15 times; in step S4, the data curves of the middle 5 impacts are taken, and the energy feedback ratio HER of the sample is calculated respectively and then the average value is taken. After such setting, the value is more reliable to ensure the reliability of the test result.
[0013] Preferably, in step S1, at least three samples are taken from the test shoes; in step S4, the average value of the energy feedback ratio HER of all the samples is obtained. This setting can ensure the reliability of the test results.
[0014] Preferably, it also includes step S5 and step S6, step S5 is to take out the sample, observe and record whether the sample surface is damaged or lost; step S6 is to make a test conclusion based on the energy feedback ratio HER and the record of step S5. Comprehensively combining HER and the surface condition of the sample after the test, a reliable test conclusion is obtained.
[0015] Preferably, the error between UM and the theoretical value should not exceed 2% to ensure the accuracy of the test results.
[0016] The present invention has the following beneficial effects: The present invention calculates the energy feedback ratio HER of the sample by obtaining the energy value UF returned by the shock absorption system and the energy value UM applied by the impact test system, and quantifies the calculation method of the material energy feedback ratio (HER). By peeling the sample, the presence of the material surface coating that affects the test results is avoided, and by limiting the thickness of the sample, the measurement results are reliable. In addition, the test steps of the present invention are simple, and the previous shock absorption test instruments can be used. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 A simplified diagram of the test instrument.
[0017] Figure 2 Schematic diagram of the impact head impacting the sample.
[0018] Figure 3 for Figure 2 Enlarged schematic diagram of part A in the middle.
[0019] Figure 4 It is the displacement-force curve of a certain impact process.
[0020] Main component symbols: Supporting and fixing platform 1, impact device 2, device body 21, force sensor 22, impact head 23, sample 3. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0022] The present invention discloses a method for testing the energy feedback performance of microporous materials, which comprises the following steps: S1. Obtain sample 3 from the sole of the test shoe, preferably at least 3 samples. Sample 3 is circular with a diameter of not less than 65 mm, or sample 3 is square with a side length of not less than 65 mm. In addition, the thickness w of sample 3 is about 25 mm, preferably greater than 25 mm. The obtained sample 3 is as integrated as possible to better ensure the test. In the case where the sole thickness w of the test shoe is less than 25 mm, it can be composed of multiple sole slices stacked, but the flatness of each layer of sample 3 needs to be ensured.
[0023] S2. Peel the sample 3. The thickness w of the sample 3 after peeling is 25±1 mm. Peeling can remove the film on the surface of the sample 3 to prevent the film from affecting the test results. For the sample 3 with a laminated structure, each layer of the sole slice should be peeled.
[0024] S3. This step is performed on an existing shock absorption test instrument, such as Figure 1-3 As shown, it generally has a supporting and fixing platform 1 and an impact device 2. The sample 3 is fixed on the supporting and fixing platform 1, and the test part of the sample 3 is positioned (that is, the center of the sample 3 is facing the impact head 23, and the impact head 23 is located directly above the sample 3). It is necessary to ensure that the sample 3 will not shift during the test. Generally speaking, the area of the supporting and fixing platform 1 needs to be larger than that of the sample 3 to ensure reliable support of the sample 3. The impact device 2 includes a device body 21, a force sensor 22 and an impact head 23 from top to bottom. The impact head 23 is a cylinder with a diameter of 45±0.1mm. The bottom edge of the impact head 23 is provided with a chamfer with a width of 1.0±0.25mm or a fillet with a radius d of 1.0±0.25mm. The mass of the impact head 23 does not exceed 0.2kg, and the total mass of the impact device 2 is 8.5-12kg. The impact device 2 is adjusted so that the drop height h from the impact head 23 to the sample 3 is 50-80mm.
[0025] At a temperature of 23±2℃ and a relative humidity of 50±4%, start the test instrument, so that the impact device 2 freely falls from a set height to impact the sample, and cycles N times, the impact cycle period is 2±0.1s, N is a positive integer, the test instrument records the energy absorption curve and energy release curve of the sample 3 during each impact process, preferably, N=15, and only the data of the middle five times are taken. The energy absorption curve and energy release curve of the sample 3 are the displacement-force curves of the sample 3 during the impact process, see Figure 4 , which is a displacement-force curve diagram recorded in a certain impact process, wherein curve AC refers to the energy absorption curve of sample 3, and curve BC refers to the energy release curve of sample 3. The impact process is absorption first and then release, that is, curve AC appears first and then curve BC appears.
[0026] The displacement-force curve can be used to determine the maximum impact tolerance of sample 3. If the AC line is close to the displacement-force curve (curve AC) or is within the error range of the displacement-force curve (curve AC), it means that the slope is valid and the thickness of sample 3 is suitable for the corresponding impact force; if the AC line is outside the error range of the displacement-force curve (curve AC), it means that the thickness of sample 3 is not suitable for the corresponding impact force, that is, the thickness of the sole is not suitable for sports with the impact force.
[0027] S4. Calculate the energy value UM applied by the impact device (2) according to the energy absorption curve of the sample (3), calculate the energy value UF returned by the sample (3) according to the energy release curve of the sample (3), and calculate the energy feedback ratio HER of the sample (3), HER=UF / UM*100% Steps S2 and S3 are performed on all samples 3.
[0028] S4. Calculate the energy value UM applied by the impact device 2 according to the energy absorption curve of the sample 3, calculate the energy value UF returned by the sample 3 according to the energy release curve of the sample 3, and calculate the energy feedback ratio HER of the sample 3, HER=UF / UM*100%, and then take the average value. Assuming that the total number of samples 3 is 3, there are 3*5=15 data in total, and the average value of the 15 data can reliably characterize the energy feedback ratio. It should be noted that in each set of data, the error between UM and the theoretical value should not exceed 2% to ensure the accuracy of the test results.
[0029] S5. Take out sample 3, observe and record whether the surface of sample 3 is damaged or lost.
[0030] S6. Draw a test conclusion based on the energy feedback ratio HER and the record of step S5. Combining HER and the surface condition of the test sample 3 after the test, a reliable test conclusion is obtained.
[0031] The present invention calculates the energy feedback ratio HER of sample 3 by obtaining the energy value UF returned by the shock absorption system and the energy value UM applied by the impact test system, and quantifies the calculation method of the material energy feedback ratio (HER). By peeling sample 3, the presence of the film on the surface of the material is avoided to affect the test results. At the same time, by limiting the thickness of sample 3, the measurement results are reliable. In addition, the test steps of the present invention are simple, and the previous shock absorption test instruments can be used.
[0032] In this case, the thickness w of sample 3 is limited to 25±1mm based on the following test. A plurality of samples 3 with different thicknesses (sample 3 is round and has a diameter of 65mm) are prepared with EVA material for simulation test (the mass of impact device 2 is 8.5kg, and the drop height of impact head 23 is h=50mm). The test results are shown in Table 1. It can be seen from Table 1 that after the thickness w of sample 3 exceeds 25mm, the HER value tends to be stable, and the influence of the thickness of sample 3 on HER is relatively low; while for materials with a thickness w of sample 3 lower than 25mm, the impact energy exceeds its limit and cannot be accurately evaluated, so 25mm is selected.
[0033] Table 1
[0034] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for testing the energy feedback performance of microporous materials, characterized in that: The following steps are involved: S1. Obtain a sample from the sole of the test shoe (3); S2. Peeling the sample (3). The thickness of the sample (3) after peeling is 25±1 mm. S3, fixing the sample (3) on the testing instrument and locating the test part of the sample (3); starting the testing instrument so that the impact device (2) freely falls from a set height to impact the sample, and the cycle is N times, where N is a positive integer; the testing instrument records the energy absorption curve and energy release curve of the sample (3) during each impact process; S4. Calculate the energy value UM applied by the impact device (2) according to the energy absorption curve of the sample (3), calculate the energy value UF returned by the sample (3) according to the energy release curve of the sample (3), and calculate the energy feedback ratio HER of the sample (3), HER=UF / UM*100%.
2. The method for testing the energy feedback performance of microporous materials according to claim 1, characterized in that: In step S1, the sample (3) is circular with a diameter of not less than 65 mm, or the sample (3) is square with a side length of not less than 65 mm.
3. The method for testing the energy feedback performance of microporous materials according to claim 1, characterized in that: In step S1, the sample (3) is an integral structure or a laminated structure.
4. The method for testing the energy feedback performance of microporous materials according to claim 1, characterized in that: In step S3, the mass of the impact device (2) is 8.5-12 kg, the drop height from the impact device (2) to the sample (3) is 50-80 mm, and the impact cycle period is 2±0.1 s.
5. The method for testing the energy feedback performance of microporous materials according to claim 1, characterized in that: The impact device (2) comprises, from top to bottom, a device body (21), a force sensor (22), and an impact head (23); the impact head (23) is a cylinder with a diameter of 45±0.1 mm; the bottom edge of the impact head (23) is provided with a chamfer with a width of 1.0±0.25 mm or a fillet with a radius of 1.0±0.25 mm; the mass of the impact head (23) does not exceed 0.2 kg.
6. The method for testing the energy feedback performance of microporous materials according to claim 1, characterized in that: Step S3 is performed at a temperature of 23±2° C. and a relative humidity of 50±4%.
7. The method for testing the energy feedback performance of microporous materials according to claim 1, characterized in that: In step S3, the impact cycle is performed 15 times; in step S4, the data curves of the middle 5 impacts are taken, and the energy feedback ratio HER of the sample (3) is calculated respectively and then the average value is taken.
8. The method for testing the energy feedback performance of microporous materials according to claim 1, characterized in that: In step S1, at least three samples are taken from the test shoes; in step S4, the average value of the energy feedback ratio HER of all the samples (3) is calculated.
9. The method for testing the energy feedback performance of microporous materials according to claim 1, characterized in that: The method further comprises steps S5 and S6. Step S5 is to take out the sample (3), observe and record whether the surface of the sample (3) is damaged or lost. Step S6 is to draw a test conclusion based on the energy feedback ratio HER and the record of step S5.
10. The method for testing the energy feedback performance of microporous materials according to claim 1, characterized in that: The error between UM and the theoretical value shall not exceed 2%.
Citation Information
Patent Citations
Device for detecting horizontal impact load
CN110068441A
Horizontal low-speed impact test device for soft material
CN118168955A
Jump assisting soles in sports
CN202774441U
High strength lightweight mortar composition comprising pre-wetted artificial lightweight fine aggregate with recycled water of ready mixed concrete
KR1020200125141A
